Authoritarian/democracy waves in theory of democratic transition - Шаповаленко, М. В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
The article provides an overview of the main directions of research undemocratic political regimes in modern political science. New stage in the study of authoritarianism is seen as a consequence of the steady equilibrium in world dynamics and outcome of the third wave of democratization. Focusing on the classification schemes developed by modern researchers, the article gives the main achievements in the knowledge of modern forms of autocracies, and discussion questions that still await resolution.